Potential of Wellness Spa Business in the Eastern Region of Thailand to Be a Hub of Health Tourism - Chongsitjiphol, Srisuda; Wongmonta, Seri (Nimitmai Review Journal, 2021)
This research aims at studying 1) the potential of wellness spa businesses in the Eastern region of Thailand, innovation in the industry, management competency, and government supports to enhance the competitiveness of the wellness spa industry. This is a qualitative research employing in-depth interviews and focus group interviews to collect data. The key informants are 60 people involved in the development and the promotion of wellness spa businesses in 4 provinces of the region. A total number of 60 respondents are selected with purposive selection. They are public officers, entrepreneurs, leading community members, scholars, and tourists who have used wellness spa services.The findings reveal that key success factors of the wellness spa industry in the region are Thainess hospitality, certified professional employees with expertise, menu of a variety of choices, and attractive tourism resources. In order to create competitiveness in the global arena, wellness spa businesses in the region should be positioned as enterprises offering holistic wellness spa services for physical, mental, social, and spiritual health. Other than health services, there should be services in the areas of beauty, nutrition, weight loss, body shaping, and anti-aging. Employees must be trained on massage skills, salesmanship skills, service skills, interactive skills, and language proficiency. The government supports are strongly needed. The supports include 1) training employees, 2) developing management competency, launching aggressive marketing and integrated marketing communication campaigns. Public officers should change their mindset from working with a controlling concept to a supporting concept. They should act like coaches, mentors, and advisors to help enhance competitiveness of the wellness spa industry. In order for Thailand to become an international hub of health tourism, the government must execute brand equity building for Thailand health tourism, while entrepreneurs must build brand equity for their own businesses.